Evaluation of postpartum intrauterine contraceptive devices (IUCD) insertion: 5 years study - Antaratani, Ramalingappa C.; D., Vinay Raju; K., Sanjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The intrauterine contraceptive device (IUD) primarily in the form of copper T is used by more than 150 million women around the world making it the most widely used reversible method of contraception with a remarkably low failure rate of less than 1 per 100 women in the first year of use for cu T 380 A. It is more suitable for a country like India which is in urgent need of population control methods. Methods: A Prospective observational study was under taken where in a series of women who delivered either vaginally or through caesarean section during the period of November 2013 to October 2017 in the Department of Obstetrics and Gynecology, Karnataka Institute of Medical Sciences, Hubli counseled for PPIUCD insertion were included in the study. Mothers who were suffered from Chorioamnionitis, Puerperal sepsis, Postpartum haemmorrhage, PROM more than 18 hours, extensive genital trauma, uterine abnormalities, Multiple sexual partners and obstructed labour were excluded from the study. Since it was a time bound study, a total of 16009 cases were enrolled in the study after counseling them. Results: A total of 16009 women were counseled to undergo PPIUCD, out which 5144 women accepted for PPIUD amounting to a total acceptance rate of 32.1%.Out of the 10865 women who did not accept device, the reason for non-acceptance preference another contraception 60%, family opposition was reason in 21% of women, while 08% of women had side effects from their previous use. 11% of women said that they were not desire to use contraception. Conclusions: Family planning and mother and child health services are supplied to the people free of cost in India. Use of an intrauterine device is simpler , less expensive, and immediately reversible.